Analysis of Work Environment Factors Affecting Employee Performance at PT Bank Sumut Syariah KCP Binjai - Elsa Mayori Elsa; Wahyu Syarvina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Work environment means processes, systems, structures, tools or conditions in the workplace that have a favorable or unfavorable impact on individual performance. One of the factors that influence the level of success of an organization is the performance of its employees. This study aims to find out important information about work environment factors that have an influence on employee performance. Creating a work environment where productive employees are essential to increase profits for good organizations and companies. The workplace becomes an integral part of the work itself. Companies must step outside of their traditional roles to create a work environment where employees enjoy what they do, take pride in what they do, in order to reach their potential. The population in this study were employees of PT Bank Sumut Syariah KCP Binjai. The number of samples used in this study were 8 employees using the field method. The research conducted is descriptive qualitative research, namely observations and interviews conducted by analyzing data sourced from employees of PT Bank Sumut Syariah KCP Binjai relating to any work environment factors that affect the performance of Bank Sumut Syariah KCP Binjai employees. The results of the study prove that the physical and non-physical environment has an influence on employee performance, and corporate culture and supporting facilities greatly affect employee performance.